Recovering the Christian Practice of Dying: A Response to Stanley Hauerwas’ "Finite Care in a World of Infinite Need" - Cramer, David C. (Christian scholar's review, 2012)
In his 2009 essay, “Finite Care in a World of Infinite Need” (CSR 38.3 [Spring 2009]: 327-333), Stanley Hauerwas suggests that, given the unlimited health care needs and limited health care resources in the U.S., Christians need to imagine an integrally Christian practice of medicine, which may include refusing potentially life-saving treatments. In this response essay, David C. Cramer argues that Hauerwas’ suggestion is best understood in terms of the Christian practices articulated by John Howard Yoder in his work Body Politics. As with Yoder’s practices, so the Christian practice of dying is both a religious act of the church and a public act with concrete, observable social implications.